Toward Evidence-Based Practice. Issue 3 (May 2022) - Rohan, Annie J.; Adams, Ellise D.; Giurgescu, Carmen; Hayman, Laura L.
Abstract : Experts suggest how 6 research articles can be used in nursing practice.